THE EFFECT OF PEDAGOGICAL AND PERSONAL COMPETENCIES ON TEACHERS’ PROFESSIONAL COMPETENCE, WITH ORGANIZATIONAL CULTURE AS A MEDIATING VARIABLE, AT SMPN 14 IN SERANG CITY - Hamidah Hamidah; Rohmah Rohmah; Fitria Fitria; Astari Astari; Mutoharoh Mutoharoh (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the influence of pedagogical competence and personality competence on teacher professional competence, with organizational culture as a mediating variable at SMPN 14, Serang City. Using a quantitative approach, data were collected through questionnaires distributed to 30 teachers as respondents. The results showed that pedagogical and personality competencies have a positive effect on teacher professionalism. Organizational culture was found to play a significant role as a mediator that strengthens this relationship. These findings imply the importance of strengthening a conducive school culture to optimize teacher potential